The Perception of Teaching, Learning Styles and Commitment to Learning and Their Influence on the Practice of Physical Activity and Eating Habits Related to the Mediterranean Diet in Physical Education Students - Fernandez-Ortega, Carmen; González-Bernal, Jeronimo; Gonzalez-Bernal, Sergio; Trigueros, Ruben; Aguilar-Parra, José M.; Minguez-Minguez, Luis A.; Obregon, Ana I.; De La Fuente Anuncibay, Raquel (Frontiers in Psychology, 2022)
Childhood obesity, linked to a sedentary lifestyle and an unbalanced diet, is one of the main problems in today's Western societies. In this sense, the aim of the study was to analyse students' perceived satisfaction in physical education classes with learning strategies and engagement in learning and critical thinking as determinants of healthy lifestyle habits. The study involved 2,439 high school students aged 12-18 years (M = 14.66, SD = 1.78). Structural equation modelling was conducted to analyse the predictive relationships between the study variables. The results showed that teaching, teaching mastery, and cognitive development are precursors to deep thinking on the part of students, indicators of the adoption of healthy lifestyle habits. These results reflect the importance of the methodology adopted by the teacher in order to positively influence the students' habits.